Effects of Counseling on the Quality of Life of MDR Lung TB Patients - Baharuddin Condeng (Poltekkes Kemenkes Palu, 2023)
Research shows initiatives to combat the TB virus. Patients with MDR-Lung Tuberculosis are worried about their quality of life, according to recently completed research in Indonesia. Patients with MDR-TB may benefit from counseling to enhance their quality of life. Study aims to analyze effect of counseling on changes in the quality of life of MDR-TB patients. A quasi-experimental design with a randomized pretest and posttest control group is used in this kind of research. 38 patients from the Undata Palu Hospital who were randomly chosen between May and November 2022 made up the study's samples. The data were then analyzed using the Wilcoxon test, the Mann Whitney test, and the two mean difference tests. Each participant receives counseling sessions seven times over the course of a six-month period. Counseling using the SOWAN approach is supported by observation, well-being, action, and nursing. The research ethics number for this study is 0011.7/KEPK-KPK/IV/2022 This research received a research ethics number 0011.7/KEPK-KPK/IV/2022 from the Research Ethics Commission of the Ministry of Health Poltekkes Palu. The result of this research show it has been shown that counseling MDR lung TB patients at Undata Palu Hospital improves their quality of life to the point that ongoing counseling is necessary for MDR lung TB patients and can reduce the occurrence of MDR TB.